2000
DOI: 10.1128/iai.68.6.3720-3723.2000
|View full text |Cite
|
Sign up to set email alerts
|

Gamma Interferon Is Essential for Clearing Mycobacterium genavense Infection

Abstract: Factors determining the in vivo replication of the opportunistic pathogen Mycobacterium genavense are largely unknown. Following intravenous injection of a patient isolate, M. genavense could not be recovered by culture or detected by PCR in the livers or spleens of infected BALB/c mice. In contrast, M. genavense was found to chronically persist and multiply in the livers and spleens of intravenously infected syngeneic gammainterferon-gene-deficient (GKO) mice as evidenced by acid-fast stains of infected tissu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…Others have also shown that cytokines and iNOS were required for granuloma formation and control of tuberculous infection in C57BL/6 mice (1). Although less direct in its association, both the TNF-␣ p55 receptor knockout mice and the IFN␥ knockout mice had little NO production and showed poorly formed or absent granuloma formation with mycobacterial or paracoccidioidomycosis infection (41,42). Treatment of Salmonella typhimurium-infected BALB/c mice with anti-IL-12 resulted in reduced IFN␥ and iNOS expression, and disruption of granuloma formation (43).…”
Section: Discussionmentioning
confidence: 98%
“…Others have also shown that cytokines and iNOS were required for granuloma formation and control of tuberculous infection in C57BL/6 mice (1). Although less direct in its association, both the TNF-␣ p55 receptor knockout mice and the IFN␥ knockout mice had little NO production and showed poorly formed or absent granuloma formation with mycobacterial or paracoccidioidomycosis infection (41,42). Treatment of Salmonella typhimurium-infected BALB/c mice with anti-IL-12 resulted in reduced IFN␥ and iNOS expression, and disruption of granuloma formation (43).…”
Section: Discussionmentioning
confidence: 98%
“…A parallel intravenous injection of M. genavense into immunocompetent and gamma interferon-deficient mice produced persistent infection of the liver and spleen only in the latter animals, suggesting that the virulence of the species is not sufficiently high for it to survive and spread in the presence of gamma interferon-activated macrophages (35). However, its persistence in gamma interferon-deficient mice closely resembles the disseminated infection of M. genavense in immunodeficient patients.…”
Section: Genavensementioning
confidence: 89%
“…4,5 In immunocompetent mice the most important source of IFN-␥ is Th1 cells. In a recent publication, it was demonstrated that the development of T-cell-independent granuloma is reliant on the induction of IFN-␥ release by natural killer (NK) cells.…”
Section: Formation Of Granulomas In the Lungs Of Severe Combined Immumentioning
confidence: 99%